Forced Displacement: Impact on Rural Women in India. Issue 1 (June 2018) - Kumar, Sudesh; Mishra, Anindya J.
The article explores the loss of traditional occupations and customary rights among displaced women and the socio-economic consequences of being forced into the labour market in the absence of a uniform rehabilitation and resettlement policy in India.